Revealed Comparative Advantage and Competitiveness: A Case Study for India in Horticultural Products - Bhattacharyya, Ruma (TNEU, 2012)
This paper seeks to quantify the extent to which India has a comparative advantage in vegetable, fruits and flower trade in the Asian, EU and North American (USA & Canada) markets as compared to selected other South East Asian countries. To study India’s competitiveness two widely used indexes are calculated: the revealed comparative advantage (RCA) and the comparative export performance (CEP) index. In addition, import demand functions of the EU are estimated for rival countries for particular commodities, like onion, mango and fresh flowers. Using regression analysis it is hypothesized that if India is a competitor for these countries, its price will have a statistically significant effect on export demand functions. Both index and regression results indicate that India has a strikingly high comparative advantage in the vegetable and fruit markets in the EU but this is not the case in the flower market.
Keywords: Horticulture; Revealed Comparative Advantage; Comparative Export Performance